A külföldi egyetemek szerepe a protestáns természetjog hazai térnyerésében - P. Szabó, Béla (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The study, applied different methodological paths, attempts to revive and highlight data and facts from the first half of the 18th century that may reveal, in the most striking way, the ways in which Protestant students at Western universities could have acquired, used or passed on their superficial or in-depth knowledge of natural law. The universities of Halle and Frankfurt an der Oder, as well as those of the Netherlands, were the places where liberal arts and law students from the Carpathian Basin were most intensively exposed to the natural law doctrines of Grotius and Pufendorf, listening to Thomasius, Heineccius and other German and Dutch professors. The survey, which is by no means exhaustive, is based on data from university visits, letters reporting on studies and analyses of academic works.